A construção de um arcabouço orientador crítico para curricularizar a extensão universitária: uma contribuição fundamentada em valores CTS - Miranda, Frederico Severo (2024)
Resolution No. 7 of December 18, 2018 is a federal law document that made the implementation of extension actions in Brazilian higher education courses mandatory, in other words, the outreach needs to be included in university curricula. However, the Resolution No. 7 does not elucidate how, in fact, to achieve its pre-established dictates, which opens up several possibilities when carrying out an outreach, such as, for example, an alienating/resigned outreach or an emancipatory/critical outreach. It is noteworthy that in this thesis, the outreach is understood as a path to social emancipation and, given this fact, it is important that the research is supported by a critical theoretical basis só that it can reach its full emancipatory potential. That said, the following research question is raised: how to implement the curricularization outreach in a Brazilian higher education course considering the critical perspective of studies in Science, Technology and Society in a way that encourages the search for democratic paths that aim to meet social demands locations? Therefore, to answer the research question, a systematic bibliographic review was carried out in eight digital libraries considering a time span of 10 years. Documentary research was also developed on the history of outreach from a critical perspective of studies in Science, Technology and Society and another documentary research regarding the guidelines for extension actions at the Federal Technological University of Paraná. Furthermore, a theoretical conceptual model was created based on the application of categorical content analysis considering Resolution no. 7. From the intersection of the previous steps, as a final result and novelty of this thesis, a critical guiding framework was developed whose objective is to answer the research question. The aforementioned framework has five stages constructed from the values present in critical studies in Science, Technology and Society and guidelines from Resolution no. 7 itself. It is noteworthy that its validation was carried out by the coordination of the Bachelor’s degree in Information Systems at the Federal Technological University of Paraná and, in addition, its partial appropriation (practical execution) was carried out in a private sector college. Given the scenario exposed above, it is concluded that the critical guiding framework can be used as a way to carry out the curricularization outreach considering a critical vision aimed at social emancipation.